MOTIVASI TIM SEPAKBOLA - Atiq, Ahmad (Universitas Tanjungpura, 2013)
All team members must be motivated to work as part of a group of highly motivated and compact. Scientific approach to help coaches improve teamwork menuaikan task. There are several keys to motivating a team. compactness can be developed especially through the use of a perceptual approach to motivate and by always emphasizing its important thoughts and behavior are optimistic. in general, and the threat of reprimand is not productive, but if used wisely may be beneficial. Teamwork plays an important role in the motivation tim.kekompakan can be improved by limiting their membership on the team that can meet the entry requirements will ketat.kekompakan also greater in small and homogeneous group and the group that mempuyai clear goals, especially if the achievement of goals is threatened by an opponent. Important task of the coach is to develop cohesiveness tim.dengan determine the factors that affect the cohesiveness, more positively or negatively, the coach can draw up a team of highly motivated unit unit. If it's done well then small teams or large will easily earn achievements with goals in the team ingginkan.sebuah not easily handled if the coach does not have special skills and are able to provide guidance on an ongoing basis in demand means that coaches have expertise with good multi can educate and train. Kata Kunci : Motivasi, Tim Sepakbola